2007
DOI: 10.1007/s00299-007-0315-x
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of ornamental Prunus spp. and GF305 peach, a Prunus viral indicator

Abstract: A micropropagation approach was developed for nine ornamental Prunus species, P. americana, P. cistena, P. glandulosa, P. serrulata 'Kwanzan', P. laurocerasus, P. sargentii, P. tomentosa, P. triloba, P. virginiana 'Schubert', commercially important in North America, and GF305 peach, commonly used for Prunus virus indexing. The micropropagation cycle based on proliferation of vegetative tissues includes establishment of tissue culture through introduction of shoot meristems in vitro, shoot proliferation, root i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 18 publications
6
35
2
3
Order By: Relevance
“…The first attempts to propagate Prunus species were successful during the 1960s (Martínez-Gomez et al, 2005) and, after that, economically important species were propagated using meristems (Perez-Tornero et al, 1999;Kalinina et al, 2007), axillary buds (Muna et al, 1999) or shoot tips (Sulusoglu and Cavusoglu, 2013).…”
Section: A Achievements In Micropropagationmentioning
confidence: 99%
“…The first attempts to propagate Prunus species were successful during the 1960s (Martínez-Gomez et al, 2005) and, after that, economically important species were propagated using meristems (Perez-Tornero et al, 1999;Kalinina et al, 2007), axillary buds (Muna et al, 1999) or shoot tips (Sulusoglu and Cavusoglu, 2013).…”
Section: A Achievements In Micropropagationmentioning
confidence: 99%
“…Other cytokinins such as zeatin, 2iP and kinetin have also been tested in several studies and have generally been found to be less active [28]. The development of axillary buds as a multiplication method has been used in some fruit cultivars [29] as is one of the most effective methods of maintaining the genetic stability of cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…have been used for somatic organogenesis and embryogenesis, protoplast fusion, and hybridization (Druart, 1980(Druart, , 1999Jones et al, 1984;Garin et al, 1997;Tang et al, 2000). It has also been exploited in agricultural practices, horticulture, forestry and industry in order to achieve mass propagation of virus free plants (Neil and Neil, 2000;Akita et al, 2006;Feeney et al, 2007;Kalinina and Brown, 2007;Ružić et al, 2010). Many of these areas include working within the in vitro culture of the callus and one of the direction of the in vitro culture development are grafting compatibility of the rootstock and scion (Errea et al, 1994;2001;Nito et al, 2005;Todić et al, 2005).…”
Section: Culture Conditionsmentioning
confidence: 99%
“…Flowering cherries (members of the Prunus subgenus Cerasus; Rosaceae) have been cultivated for more than 1000 years (Kato et al, 1999) and the economic and commercial importance is based on their attractive appearance, extensive vegetation, unpretentious growth conditions and high adaptation abilities (Kalinina and Brown, 2007). While research on the improvement of agronomic traits has been extensively conducted in the edible Prunus species (Caponeti et al, 1971;Jones and Hopgood, 1979;Garin et al, 1997;Miletić et al, 2008;Ružić et al, 2010;Mahdavian et al, 2011;Druart, 2013;Dorić et al, 2014) study of ornamental representatives of this genus is done on a much smaller scale, most probably due to fewer economic benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation